Barbarian tides : time frame--1500-600 BC - Time-Life Books (Alexandria, Va. : Time-Life Books, 1987)
Describes the historical events and the various civilizations that flourished throughout the world, with emphasis on the Mediterranean area, from 1500 to 600 B.C.
Aggressive empires--Egypt's golden age--The Greek cruicible--Mediterranean traders--Asian evolutions--Awakening in the Americas.
Includes index.
Bibliography: p. 175.
Keywords: World history; Europe -- History -- To 476.; Europe -- History -- To 476.